Nutritional status disorders in women with lichen sclerosus of the vulva - V.V. Dunaievska; E.H. Manzhalii (Publishing House TRILIST, 2021)
Research objective: to determine the characteristics of nutritional status (NS) in women of reproductive age with typical clinical signs of lichen sclerosus of the vulva (LSV) using key NS parameters. Materials and methods. The study included 75 women with average age 31.3 ± 1.3 years. 50 women were diagnosed with LSV and NS disorders (main group), and 25 women were practically healthy (control group). Information about all patients was collected through direct interviews, clinical examination and study of medical records. The presence of anogenital pruritus, soreness or burning, dryness, dyspareunia, urinary disturbances, perianal and/or intestinal symptoms, inflammatory bowel disease, thyroid dysfunction and tenderness, and other comorbidities were recorded. NS evaluated using anthropometric, laboratory and clinical studies. Body mass index, index of nutritional risk (nutritional deficiency), vitamins, micro- and macroelements value, scatological parameters were determined in all patients, and the intestinal microflora was examined. Results. The results of the study showed a disorder of NS in most patients with LSV by all studied parameters in comparison with the control group. Thus, it was found that 60% of patients with LSV had abnormal body mass index as well as NS was observed in 72% of patients. In addition, patients with LSV also had a higher deficiency of vitamins D and B12, and some important micro- and macronutrients. The results of the coprological study showed the neutral fats in feces, unchanged muscle fibers, extracellular and intracellular starch, decreased levels of bifidobacteria and lactobacilli in 68-74% of patients and opportunistic bacteria and fungi in 30-46% of women in the main group. Conclusions. Thus, the results of this study indicate the association between the abnormal NS and LSV. However, further research is needed to assess the course of the underlying disease and to analyze the metabolic pathways that lead to disorders of lipid, carbohydrate and protein metabolism in target patients, to select of the correct nutrients and alternative treatments.